Generating Electricity using PV/FC Hybrid System - Z Nawawi; M. A. B. Sidik; M. I. Jambak; R. F. Kurnia; A. S. Aziz; H. J. Kareem; A. Z. Abdulameer; M. A. A. Aziz; Z Buntat; Y. Z. Arief (IAES Indonesia Section, 2015)
A reliable electrical energy supply is a prerequisitefor improving the standard economic and quality of life levels in acountry. As is the case in many countries, it is uneconomical toconnect these villages to the existing grid, the installation of standaloneelectrical power generators has become common practice. Asa result, diesel stand-alone power generators see widespread use inthese remote locales, which, whilst fit for their intended purpose,unfortunately suffer from several drawbacks, including instabilityin regards to everyday oil prices and a number of environmentalissues. The implementation of a PV/FC hybrid power system couldbe one potential alternative to help solve these problems. Therefore,this paper presents PV/FC system control strategies. This study isespecially important in terms of envisioning the future energysupply needs. By using HOMER the proposed control strategiesand suggested components of a PV/FC system would be able toproduce a satisfactory outcome.